Development of interactive learning activities in heat transfer. (15th September 2008) - Tan, F.L.; Fok, S.C.
This paper presents ongoing work at Nanyang Technological University (NTU) on the development of electronic resources for thermal-fluid courses, with a focus on the development of interactive learning activities for students to explore and discover heat transfer concepts and mechanisms. Three basic types of Java applets based on the three main types of interactive knowledge discovery activities are presented. Using these three basic applets, different interactive learning activities to assist the students in the learning of heat transfer principles are developed and discussed. The activities can aid the students in the visualisation of certain heat transfer concepts; the user interface is user friendly; and the proposed activities can enable the student to acquire thermal knowledge through interactive exploration.